The Disclosure Of Shariah Non-compliance (snc) Events By Islamic Banks In Malaysia - Marina Mohamed; Norhazlina Ibrahim (UiTM Press, Universiti Teknologi MARA, 2024)
Journal of Emerging Economies & Islamic Research, Volume11 Issue 2 Page (48–74)